2008
DOI: 10.1038/ejhg.2008.137
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection and the molecular basis of electrophoretic variation at the coagulation F13B locus

Abstract: Electrophoretic analysis of protein variation at the coagulation F13B locus has previously revealed three alleles, with alleles 1, 2, and 3 each being at high frequency in European, African, and Asian populations, respectively. To determine if this unusual pattern of interpopulation differentiation reflects local natural selection or neutral genetic drift, we re-sequenced 4.6 kb of the gene, encompassing all exons, splice junctions, and 1.4 kb of the promoter, in African, European, and Asian samples. These ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…For the F13B SNP, rs6003, the minor (95Arg) allele had a higher frequency compared to the wild type (95His) allele in white populations, which is in agreement with previous research in Nigerians (Ryan et al , ).…”
Section: Discussionsupporting
confidence: 91%
“…For the F13B SNP, rs6003, the minor (95Arg) allele had a higher frequency compared to the wild type (95His) allele in white populations, which is in agreement with previous research in Nigerians (Ryan et al , ).…”
Section: Discussionsupporting
confidence: 91%
“…For this allele, a C‐to‐G nucleotide change was identified in intron‐K (A+144G), the same variation as very recently described independently by Ryan et al. [22]. Iwata et al.…”
supporting
confidence: 70%
“…The crux of the study centers on the characterization of the FXIII-B*3 allele. For this allele, a C-to-G nucleotide change was identified in intron-K (A+144G), the same variation as very recently described independently by Ryan et al [22]. Iwata et al found that this nucleotide change activates a cryptic, efficient splicing acceptor site in intron-K, resulting in an allele-specific alternative splicing event downstream of exon XI [1].…”
mentioning
confidence: 64%
“…The functional annotations of genes identified in large-scale scans (e.g., 68) flag many as potentially of significance in disease resistance or dietary adaptations. As the vast task of identifying the functions of many genes proceeds, we anticipate many similar cases to emerge (112)(113)(114).…”
Section: Current Evidence and Problems To Solvementioning
confidence: 99%